2000
DOI: 10.1556/aalim.29.2000.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Potential indicator enzyme s at broccoli blanching tecnology

Abstract: Blanching of vegetables before freezing has some advantages as well as a number of disadvantages. Process optimization involves measuring the rate of enzyme destruction, such that the blanching time is just long enough to destroy the indicator enzyme. Eventually, peroxidases were almost universally the enzymes of choice, as they are usually the most heat-stable enzymes found in vegetables and fruits, so by the time they are inactivated no other enzymes or micro-organisms remain. But there is no evidence that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…Some researchers suggested that targeting peroxidase leads to a more severe heat treatment than is required for many vegetables and that the enzymes responsible for quality loss, which have been identified, have a lower stability than peroxidase (Reid, 1998). Recently, use of LOX as an indicator of proper blanching has been recommended as more significant in determining storage stability in frozen vegetables (Barrett & Theerakulkait, 1995;Nagy-Gasztonyi, Kardos-Neumann, & Biacs, 2000;Sheu & Chen, 1991;Williams, Lim, Chen, Pangborn, & Whitaker, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers suggested that targeting peroxidase leads to a more severe heat treatment than is required for many vegetables and that the enzymes responsible for quality loss, which have been identified, have a lower stability than peroxidase (Reid, 1998). Recently, use of LOX as an indicator of proper blanching has been recommended as more significant in determining storage stability in frozen vegetables (Barrett & Theerakulkait, 1995;Nagy-Gasztonyi, Kardos-Neumann, & Biacs, 2000;Sheu & Chen, 1991;Williams, Lim, Chen, Pangborn, & Whitaker, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…POD appears to be one of the most heat stable enzymes present in vegetables and it has been generally accepted that if POD is destroyed then it is quite unlikely that other enzymes will have survived (Halpin & Lee, 1987 enough to inactivate POD is generally more than enough to destroy the undesirable enzymes, since POD activity has not been shown to be directly responsible for quality deterioration during frozen storage of vegetables. The use of LOX as indicator of proper blanching has been recommended as more significant in determining storage stability in frozen vegetables (Williams et al, 1986;Sheu & Chen, 1991;Barrett & Theerakulkait, 1995;Nagy-Gasztonyi, Kardos-Neumann, & Biacs, 2000). LOX has been associated with quality deterioration because of its involvement in offflavor and odor production, loss of pigments such as carotenes and chlorophylls, and destruction of essential fatty acids (King & Klein, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Typical indicator enzymes are peroxidase and lipoxygenase. 120 Additionally, blanching helps remove tissue gases. For most vegetables, blanching is performed for several minutes (typically 1 to 5 min) by immersion in hot water (typically in the range of 88 to 99 °C).…”
Section: Heat Treatmentmentioning
confidence: 99%